2011
DOI: 10.1002/jcp.22939
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐133a regulates collagen 1A1: Potential role of miR‐133a in myocardial fibrosis in angiotensin II‐dependent hypertension

Abstract: MicroRNAs play an important role in myocardial diseases. MiR-133a regulates cardiac hypertrophy, while miR-29b is involved in cardiac fibrosis. The aim of this study was to evaluate whether miR-133a and miR-29b play a role in myocardial fibrosis caused by Angiotensin II (Ang II)-dependent hypertension. Sprague-Dawley rats were treated for 4 weeks with Ang II (200  ng/kg/min) or Ang II + irbesartan (50  mg/kg/day in drinking water), or saline by osmotic minipumps. At the end of the experimental period, cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
123
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 42 publications
7
123
0
1
Order By: Relevance
“…We found a significant increase in cardiac mRNA for the extracellular matrix protein Col1A1 and Fn1 by STNx, which was attenuated by ramipril treatment. Luciferase gene reporter assays performed in previous studies (9,44) have demonstrated TGF-␤ 1 and Col1A1 as direct targets of microRNA-133. Fn 1 is a direct target of microRNA-1 (61).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found a significant increase in cardiac mRNA for the extracellular matrix protein Col1A1 and Fn1 by STNx, which was attenuated by ramipril treatment. Luciferase gene reporter assays performed in previous studies (9,44) have demonstrated TGF-␤ 1 and Col1A1 as direct targets of microRNA-133. Fn 1 is a direct target of microRNA-1 (61).…”
Section: Discussionmentioning
confidence: 96%
“…Fn 1 is a direct target of microRNA-1 (61). Treatment with an ANG receptor blocker, irbesartan, upregulates microRNA-133, which, in turn, mediates the inhibition of Col1A1 and the attenuation of myocardial fibrosis in a rat model of ANG II-dependent hypertension (9). Our results suggest that increased microRNA-133 and microRNA-1 after ramipril treatment may be the molecular switch responsible for the inhibition of TGF-␤ 1 -Smad signaling, which, in turn, inhibits Col1A1 and Fn1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that angiotensin II (the main active substance in the renin-angiotensin system) can stimulate the hypertrophy of the myocardial cells and hyperplasia of the cardiac fibroblasts (Castoldi et al, 2012). However, these results cannot fully explain the mechanism of myocardial fibrosis caused by high BP (Kai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…44 Furthermore, miR-21 and -29 also mediate complex signaling in the development of renal fibrosis [45][46][47][48] and thus seem to modulate similar processes in different target organs (Figure). MiR-133a regulates collagen 1A1 expression, 49 and miR-199 also links antiapoptotic Akt signaling with β-adrenergic stimulation. 50 Finally, miR-199a-5p is regulated by signal transducer and activator of transcription 3, thereby linking cardiomyocyte and endothelial cell function.…”
Section: Studies In Other Cardiac Disease Modelsmentioning
confidence: 99%